Study of physiological parameters on development medical device in monitoring infant vital signs: A review - Muhammad Afiq Firdaus, Md Zin; Mohd Azrul Hisham, Mohd Adib (IJETAE Publishing House, 2024)
Exposure to new technology is a very effective medium in handling healthcare devices, especially for monitoring the treatment of babies. This paper provides a comprehensive review of recent developments device in monitoring infant vital signs such as heart rate, SpO2 level, and temperature of neonates. The need to monitor physiological parameters is essential for ensuring the infant’s condition is stable and healthy, especially for premature babies. The technological advancements, obstacles, and possible future directions are well discussed. A comprehensive analysis of pertinent literature illustrates the details of physiological parameters used in the present devices. Integrated devices with digital health systems can enhance newborn care and reduce the risks of infant morbidity and mortality.